Engineering promising A-π-D type molecules for efficient organic-based material solar cells. Issue 5 (24th March 2023) - Abdul Zahra, Musaddak Maher; Taban, Taleeb Zedan; Kadhim, Mustafa M.; Abdullaha, Sallal A. H.; Almashhadani, Haider Abdulkareem; Rheima, Ahmed Mahdi; Hachim, Safa K.; Ebadi, Abdol Ghaffar
ABSTRACT: Within this work, to promote the efficiency of organic-based solar cells, a series of novel A-π-D type small molecules were scrutinised. The acceptors which we designed had a moiety of N, N -dimethylaniline as the donor and catechol moiety as the acceptor linked through various conjugated π-linkers. We performed DFT (B3LYP) as well as TD-DFT (CAM-B3LYP) computations using 6-31G (d, p) for scrutinising the impact of various π-linkers upon optoelectronic characteristics, stability, and rate of charge transport. In comparison with the reference molecule, various π-linkers led to a smaller HOMO–LUMO energy gap. Compared to the reference molecule, there was a considerable red shift in the molecules under study (A1 –A4 ). Therefore, based on the analysis of energy level, A4 and A3 were shown to be promising non-fullerene acceptors with the designed donors for applications in solar cells. It is hoped that the current study would provide theoretical insights into the design and amplification of optoelectronic characteristics of suggested frameworks on a grand scale in comparison with the reference molecules.